Shared familial risk factors between autism spectrum disorder and obesity – a register‐based familial coaggregation cohort study. (8th December 2021) - Ahlberg, Richard; Garcia‐Argibay, Miguel; Hirvikoski, Tatja; Boman, Marcus; Chen, Qi; Taylor, Mark J.; Frans, Emma; Bölte, Sven; Larsson, Henrik
Abstract : Background: Meta‐analyses suggest an association between autism spectrum disorder (ASD) and obesity, but the factors underlying this association remain unclear. This study investigated the association between ASD and obesity stratified on intellectual disability (ID). In addition, in order to gain insight into possible shared etiological factors, the potential role of shared familial liability was examined. Method: We studied a cohort of 3, 141, 696 individuals by linking several Swedish nationwide registers. We identified 35, 461 individuals with ASD and 61, 784 individuals with obesity. Logistic regression models were used to estimate the association between ASD and obesity separately by ID and sex and by adjusting for parental education, psychiatric comorbidity, and psychotropic medication. Potential shared familial etiologic factors were examined by comparing the risk of obesity in full siblings, maternal and paternal half‐siblings, and full‐ and half‐cousins of individuals with ASD to the risk of obesity in relatives of individuals without ASD. Results: Individuals with ASD + ID (OR = 3.76 [95% CI, 3.38–4.19]) and ASD−ID (OR = 3.40 [95% CI, 3.23–3.58]) had an increased risk for obesity compared with individuals without ASD. The associations remained statistically significant when adjusting for parental education, psychiatric comorbidity, and medication. Sex‐stratified analyses indicated a higher relative risk for males compared with females, with statistically significant interaction effects for ASD−ID, but not for ASD+ID in the fully adjusted model. First‐degree relatives of individuals with ASD+ID and ASD−ID had an increased risk of obesity compared with first‐degree relatives of individuals without ASD. The obesity risk was similar in second‐degree relatives of individuals with ASD+ID but was lower for and ASD−ID. Full cousins of individuals with ASD+ID had a higher risk compared with half‐cousins of individuals with ASD+ID). A similar difference in the obesity risk between full cousins and half‐cousins was observed for ASD−ID. Conclusions: Individuals with ASD and their relatives are at increased risk for obesity. The risk might be somewhat higher for males than females. This warrants further studies examining potential common pleiotropic genetic factors and shared family‐wide environmental factors for ASD and obesity. Such research might aid in identifying specific risks and underlying mechanisms in common between ASD and obesity.